All-source and source-specific air pollution and 10-year diabetes Incidence: Total effect and mediation analyses in the Heinz Nixdorf recall study. (March 2020) - Lucht, Sarah; Hennig, Frauke; Moebus, Susanne; Ohlwein, Simone; Herder, Christian; Kowall, Bernd; Jöckel, Karl-Heinz; Hoffmann, Barbara
Highlights: All-source AP exposure associated with DM incidence. Traffic-specific AP exposure shows strongest association with DM. Possible mediation through decreased adiponectin levels. Abstract: Background: An increasing number of studies have been published recently on the association between ambient air pollution (AP) and incident diabetes mellitus (DM), but studies investigating source-specific AP toxicity and potential mediating pathways are rare. We investigated the associations of all-source, traffic-specific, and industry-specific outdoor AP exposure with 10-year incidence of DM and potential mediation via inflammation-associated biomarkers. Methods: Data from participants of the prospective Heinz Nixdorf Recall cohort study who attended the baseline (t0 ; 2000–2003), 5-year follow-up (t1 ; 2006–2008), and 10-year follow-up (t2 ; 2011–2015) examinations was used. For participants without DM at baseline (determined using information on physician diagnosis and glucose-lowering medication), residential long-term exposure (total, traffic-specific, and industry-specific) to particulate matter (PM2.5, PM10 ), nitrogen dioxide (NO2 ), and accumulation mode particle number concentration (PNAM ) were estimated using a chemistry transport model. Covariate-adjusted modified Poisson regression models with robust standard errors were applied to estimate relative risks (RR) for the associations between baseline AP and incident DM at t2 . Mediation analyses for adiponectin, high-sensitivity C-reactive protein (hsCRP), and interleukin-1 receptor antagonist (IL-1RA) were conducted to estimate natural direct and indirect effects. Results: Of the 4, 814 participants at t0, 2, 451 participants (mean baseline age: 58.2 years) were included in the main analysis. Interquartile range (IQR) increases in total PM10 and PNAM were associated with increased risk of DM (e.g., RR: 1.25 [95% Confidence Interval (CI): 1.02, 1.53] per 3.8 µg/m 3 PM10 ). Whereas traffic-specific exposures were associated with DM risk for all air pollutants (e.g., RR: 1.24 [95% CI: 1.06, 1.46] per 0.3 µg/m 3 PM10 ), significant associations for industry exposures were limited to NO2 and PNAM (e.g., RR: 1.24 [95% CI: 1.03, 1.49] per 230 particles/mL PNAM ). Potential mediation of the association between AP and DM was observed for adiponectin but not for hsCRP and IL-1RA. Conclusion: Our study shows that long-term exposure to total and source-specific ambient AP may increase DM risk, with consistent results observed across traffic-specific exposures. Decreases in adiponectin may play a potential role along the causal pathway.